Structural, Vibrational and Electronic Properties of cis and trans Conformers of 4-Hydroxy-l-Proline: A Density Functional Approach (Journal of Atomic and Molecular Sciences, 2021)
4-hydroxy-l-proline is formed by hydroxylation of proline, an amino acidfound in protein, whose inhibition results in hair problems in human, causing scurvydisease. We report a theoretical study on cis and trans conformers of 4-hydroxy-l-prolineusing first principle density functional approach at B3LYP/6-31+G(d,p) level.The equilibrium structures of both conformers are obtained to analyze their vibrationalproperties. The calculated vibrational modes are assigned and interpreted on the basisof potential energy distribution analysis. A good correlation has been obtained betweencalculated frequencies and corresponding experimental values from FTIR spectra.The electronic properties of both conformers are also calculated and discussed.
Keywords: 4-hydroxy-l-proline; cis-trans conformers; vibrational analysis; density functional theory.